Student-Generated Questions Fostering Sustainable and Productive Knowledge Building Discourse - Zhu, Gaoxia; Khanlari, Ahmad; Resendes, Monica (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
The role of questions in student learning is well recognized. However, the controversial issue of who should pose questions that direct inquiry continues: teachers or students? One perspective advocates that teachers generate questions as it assumes that students cannot generate high-quality questions. In contrast, Knowledge Building, a pedagogical approach that advocates transforming schools into knowledge-creation organizations, emphasizes student agency in generating authentic questions as they try to understand the world around them. This study examined the extent to which elementary students could generate questions and explore how student-generated questions help knowledge-building discourse progress. Comparing question threads (i.e., a series of online notes started with questions) and non-question threads (i.e., a series of online notes not started with questions), we noticed that questions posted by students engaged them in sustainable and progressive discourses, which is central to Knowledge Building. Moreover, the content analysis of the data revealed that the threads starting with questions were more likely to end up with productive threads than the non-question threads.